Asymptomatic Malaria and Helminths Coinfection and Its Association with Anemia among Primary School Children in Gedeo Zone, Southern Ethiopia: A Cross-Sectional Study - Feven Wudneh; Yabibal Gebeyehu; Sara Anberbir (Journal of Tropical Medicine)
Background. Asymptomatic malaria and helminths coinfection occurs mainly in the tropics and subtropics where poverty and sanitary practice favor its high prevalence. In the tropics, where malaria is endemic, helminths also thrive resulting in coinfection. This study aimed to access the prevalence of asymptomatic malaria and helminths coinfection and its contribution for anemia in primary school children of Gedeo Zone, Southern Ethiopia. Methodology. This was a cross-sectional study conducted among 413 primary school children from February to April 2020. Finger-prick blood samples were used to determine asymptomatic malaria and hemoglobin concentrations. Stool samples were collected and processed through formalin-ether concentration techniques to detect the presence of intestinal helminths. Data were double entered into Epi Data version 3.1 software and exported to SPSS version 20 for analysis. Pearson’s chi-square and correlation analysis were performed as part of the statistical analyses. Result. A total of 413 primary school children aged 6 to 16 years (mean age ± SD: 10.7 ± 2.64years) were enrolled in the study. 159 (38.5%) of school children were infected with at least one of the parasitic diseases. The overall prevalence of asymptomatic malaria and intestinal helminths was 46 (11.1%) and 113 (27.3%) respectively. Asymptomatic malaria and helminths coinfection was 29 (7%). Total of 39.1% of asymptomatic malaria-infected school children were anemic, which is statistically significant P<0.05. 15.9% of helminths-infected school children were anemic, not statistically significant P>0.05. The prevalence of anemia was 12 (41.3%) among coinfected students, which is statistically significant P<0.005. Conclusion. Asymptomatic malaria and helminths coinfection affects the health status of considerable number of primary school children in the study area. Therefore, simultaneous combat against the two parasitic infections is crucial to improve health of the school children.